Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure! Let's go through the steps step-by-step for each part of the question.
### (a) [tex]\((f \circ g)(4)\)[/tex]
This expression means we need to evaluate [tex]\(f(g(4))\)[/tex].
1. First, evaluate [tex]\(g(4)\)[/tex]:
[tex]\[ g(x) = 9x^2 + 2 \][/tex]
Substituting [tex]\(x = 4\)[/tex]:
[tex]\[ g(4) = 9 \cdot 4^2 + 2 \][/tex]
[tex]\[ = 9 \cdot 16 + 2 \][/tex]
[tex]\[ = 144 + 2 \][/tex]
[tex]\[ = 146 \][/tex]
2. Next, evaluate [tex]\(f(g(4))\)[/tex]. We already found [tex]\(g(4) = 146\)[/tex], so we need to find [tex]\(f(146)\)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
Substituting [tex]\(x = 146\)[/tex]:
[tex]\[ f(146) = 3 \cdot 146 \][/tex]
[tex]\[ = 438 \][/tex]
Therefore, [tex]\((f \circ g)(4) = 438\)[/tex].
### (b) [tex]\((g \circ f)(2)\)[/tex]
This expression means we need to evaluate [tex]\(g(f(2))\)[/tex].
1. First, evaluate [tex]\(f(2)\)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
Substituting [tex]\(x = 2\)[/tex]:
[tex]\[ f(2) = 3 \cdot 2 \][/tex]
[tex]\[ = 6 \][/tex]
2. Next, evaluate [tex]\(g(f(2))\)[/tex]. We already found [tex]\(f(2) = 6\)[/tex], so we need to find [tex]\(g(6)\)[/tex]:
[tex]\[ g(x) = 9x^2 + 2 \][/tex]
Substituting [tex]\(x = 6\)[/tex]:
[tex]\[ g(6) = 9 \cdot 6^2 + 2 \][/tex]
[tex]\[ = 9 \cdot 36 + 2 \][/tex]
[tex]\[ = 324 + 2 \][/tex]
[tex]\[ = 326 \][/tex]
Therefore, [tex]\((g \circ f)(2) = 326\)[/tex].
### (c) [tex]\((f \circ f)(1)\)[/tex]
This expression means we need to evaluate [tex]\(f(f(1))\)[/tex].
1. First, evaluate [tex]\(f(1)\)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
Substituting [tex]\(x = 1\)[/tex]:
[tex]\[ f(1) = 3 \cdot 1 \][/tex]
[tex]\[ = 3 \][/tex]
2. Next, evaluate [tex]\(f(f(1))\)[/tex]. We already found [tex]\(f(1) = 3\)[/tex], so we need to find [tex]\(f(3)\)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
Substituting [tex]\(x = 3\)[/tex]:
[tex]\[ f(3) = 3 \cdot 3 \][/tex]
[tex]\[ = 9 \][/tex]
Therefore, [tex]\((f \circ f)(1) = 9\)[/tex].
### (d) [tex]\((g \circ g)(0)\)[/tex]
This expression means we need to evaluate [tex]\(g(g(0))\)[/tex].
1. First, evaluate [tex]\(g(0)\)[/tex]:
[tex]\[ g(x) = 9x^2 + 2 \][/tex]
Substituting [tex]\(x = 0\)[/tex]:
[tex]\[ g(0) = 9 \cdot 0^2 + 2 \][/tex]
[tex]\[ = 0 + 2 \][/tex]
[tex]\[ = 2 \][/tex]
2. Next, evaluate [tex]\(g(g(0))\)[/tex]. We already found [tex]\(g(0) = 2\)[/tex], so we need to find [tex]\(g(2)\)[/tex]:
[tex]\[ g(x) = 9x^2 + 2 \][/tex]
Substituting [tex]\(x = 2\)[/tex]:
[tex]\[ g(2) = 9 \cdot 2^2 + 2 \][/tex]
[tex]\[ = 9 \cdot 4 + 2 \][/tex]
[tex]\[ = 36 + 2 \][/tex]
[tex]\[ = 38 \][/tex]
Therefore, [tex]\((g \circ g)(0) = 38\)[/tex].
### (a) [tex]\((f \circ g)(4)\)[/tex]
This expression means we need to evaluate [tex]\(f(g(4))\)[/tex].
1. First, evaluate [tex]\(g(4)\)[/tex]:
[tex]\[ g(x) = 9x^2 + 2 \][/tex]
Substituting [tex]\(x = 4\)[/tex]:
[tex]\[ g(4) = 9 \cdot 4^2 + 2 \][/tex]
[tex]\[ = 9 \cdot 16 + 2 \][/tex]
[tex]\[ = 144 + 2 \][/tex]
[tex]\[ = 146 \][/tex]
2. Next, evaluate [tex]\(f(g(4))\)[/tex]. We already found [tex]\(g(4) = 146\)[/tex], so we need to find [tex]\(f(146)\)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
Substituting [tex]\(x = 146\)[/tex]:
[tex]\[ f(146) = 3 \cdot 146 \][/tex]
[tex]\[ = 438 \][/tex]
Therefore, [tex]\((f \circ g)(4) = 438\)[/tex].
### (b) [tex]\((g \circ f)(2)\)[/tex]
This expression means we need to evaluate [tex]\(g(f(2))\)[/tex].
1. First, evaluate [tex]\(f(2)\)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
Substituting [tex]\(x = 2\)[/tex]:
[tex]\[ f(2) = 3 \cdot 2 \][/tex]
[tex]\[ = 6 \][/tex]
2. Next, evaluate [tex]\(g(f(2))\)[/tex]. We already found [tex]\(f(2) = 6\)[/tex], so we need to find [tex]\(g(6)\)[/tex]:
[tex]\[ g(x) = 9x^2 + 2 \][/tex]
Substituting [tex]\(x = 6\)[/tex]:
[tex]\[ g(6) = 9 \cdot 6^2 + 2 \][/tex]
[tex]\[ = 9 \cdot 36 + 2 \][/tex]
[tex]\[ = 324 + 2 \][/tex]
[tex]\[ = 326 \][/tex]
Therefore, [tex]\((g \circ f)(2) = 326\)[/tex].
### (c) [tex]\((f \circ f)(1)\)[/tex]
This expression means we need to evaluate [tex]\(f(f(1))\)[/tex].
1. First, evaluate [tex]\(f(1)\)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
Substituting [tex]\(x = 1\)[/tex]:
[tex]\[ f(1) = 3 \cdot 1 \][/tex]
[tex]\[ = 3 \][/tex]
2. Next, evaluate [tex]\(f(f(1))\)[/tex]. We already found [tex]\(f(1) = 3\)[/tex], so we need to find [tex]\(f(3)\)[/tex]:
[tex]\[ f(x) = 3x \][/tex]
Substituting [tex]\(x = 3\)[/tex]:
[tex]\[ f(3) = 3 \cdot 3 \][/tex]
[tex]\[ = 9 \][/tex]
Therefore, [tex]\((f \circ f)(1) = 9\)[/tex].
### (d) [tex]\((g \circ g)(0)\)[/tex]
This expression means we need to evaluate [tex]\(g(g(0))\)[/tex].
1. First, evaluate [tex]\(g(0)\)[/tex]:
[tex]\[ g(x) = 9x^2 + 2 \][/tex]
Substituting [tex]\(x = 0\)[/tex]:
[tex]\[ g(0) = 9 \cdot 0^2 + 2 \][/tex]
[tex]\[ = 0 + 2 \][/tex]
[tex]\[ = 2 \][/tex]
2. Next, evaluate [tex]\(g(g(0))\)[/tex]. We already found [tex]\(g(0) = 2\)[/tex], so we need to find [tex]\(g(2)\)[/tex]:
[tex]\[ g(x) = 9x^2 + 2 \][/tex]
Substituting [tex]\(x = 2\)[/tex]:
[tex]\[ g(2) = 9 \cdot 2^2 + 2 \][/tex]
[tex]\[ = 9 \cdot 4 + 2 \][/tex]
[tex]\[ = 36 + 2 \][/tex]
[tex]\[ = 38 \][/tex]
Therefore, [tex]\((g \circ g)(0) = 38\)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.